A resin-infiltrated ceramic composite material and its preparation method and application
Through the resin penetration of the ceramic composite material with a multi-layer structure, the combination of porous ceramic skeleton and resin is used to solve the shortcomings of the existing dental composite materials in light transmittance and color gradient, and the natural gradient effect from the cut end to the neck is achieved, which significantly improves the aesthetic restoration effect.
Patent Information
- Application Number
- CN202411982621.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
Existing dental composites have shortcomings in light transmittance and color gradient, resulting in poor aesthetic restoration.
A resin permeable ceramic composite material is adopted with a multi-layer structure. Each layer includes a porous ceramic skeleton and a resin permeated therein. By adjusting the light transmittance and color difference of each layer, a natural gradient effect from the cut end to the neck is achieved.
The natural light transmittance and color gradient from the cut end to the neck are achieved, which significantly improves the aesthetic restoration effect.
Smart Images

Figure BDA0005221872880000181 
Figure BDA0005221872880000191 
Figure BDA0005221872880000201
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of dental materials, and in particular to a resin-infiltrated ceramic composite material and a preparation method and application thereof. Background Art
[0002] Common dental restoration materials are divided into all-ceramic materials, resin materials and machinable composite materials. Common all-ceramic materials include zirconia, alumina, glass ceramics and feldspar porcelain materials. Among them, zirconia materials have good biocompatibility, high aesthetics and excellent mechanical properties, but they are hard and brittle, causing severe wear on the opposing teeth and the risk of fracture of the restoration. Glass ceramic materials have high light transmittance and aesthetics, but they are brittle and prone to edge chipping during processing. The strength and hardness of feldspar porcelain materials are generally low, and the restoration shrinks greatly during sintering, which can easily cause the restoration to be difficult to place. Common resin materials are mostly acrylic resins. Due to the low mechanical properties of pure resin materials, machinable resins are mostly used as temporary restoration materials or model materials. Machinable composite materials are usually composed of inorganic fillers and resins. Their elastic modulus is close to that of dentin, causing less wear on the opposing teeth, and have good biocompatibility and less irritation to the oral cavity. Therefore, they can be used as the preferred material for anterior teeth, single crowns and inlay restorations.
[0003] Cuttable composite materials can be roughly divided into two categories according to the different preparation processes. One category is based on resin as the matrix, and the inorganic ceramic powder is mixed and dispersed into the resin matrix. The obtained composite resin is formed by high temperature and high pressure thermal curing. The other category is based on porous ceramics as the matrix, and the resin penetrates into the porous ceramics. In this material, the porous ceramic skeleton and the resin matrix penetrate each other to form an interpenetrating double cross-linked network structure. This interpenetrating double cross-linked network structure can make the continuous inorganic phase and organic phase better complement each other, thereby improving the mechanical properties of the material. The physical properties of composite materials (such as strength, fracture toughness and elasticity) are not only related to the content ratio of organic / inorganic components, but also to the spatial distribution of organic / inorganic phases. On the whole, with porous ceramics as the matrix, the mechanical properties of the resin penetrating into the ceramics are better.
[0004] The color of a person's natural teeth changes during their growth process. From the neck to the incisor, the color gradually becomes lighter and the transparency gradually increases. The corresponding dental restoration materials also need a layered gradient effect to better achieve the simulation effect. However, the mechanical properties of the dental composite materials currently available on the market meet the requirements, but their light transmittance is low, the transparency does not change from the incisor to the neck, and the color transition is unnatural, which greatly affects the aesthetic restoration effect of veneers and anterior single crowns. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a resin-infiltrated ceramic composite material and its preparation method and application. The resin-infiltrated ceramic composite material provided by the present invention has the effect of gradual change of light transmittance and color from the incision end to the neck, and the transition is natural, and the aesthetic restoration effect is good.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a resin-infiltrated ceramic composite material, characterized in that it is composed of a multi-layer structure, each layer comprising a porous ceramic skeleton and a resin infiltrated in the pore structure of the porous ceramic skeleton;
[0008] From top to bottom, the light transmittance of each layer of the resin-infiltrated ceramic composite material increases successively, the absolute value of the difference in light transmittance between two adjacent layers is 0.5-10%, and the absolute value of the difference in light transmittance between the uppermost layer and the lowermost layer is greater than 3%;
[0009] From top to bottom, the colors of the layers of the resin-infiltrated ceramic composite material gradually become lighter, the color difference between two adjacent layers is 0.5-11, and the color difference between the uppermost layer and the lowermost layer is 1-30.
[0010] Preferably, the porous ceramic skeleton is obtained by molding several layers of materials and then sintering them;
[0011] Measured in percentage by mass, each layer of material in the porous ceramic skeleton independently includes 0-30% colorant, 0-20% toughening agent and the remainder of ceramic powder; and the darkest material layer is the topmost layer, and from top to bottom, the mass proportion of the colorant in the several layers of material decreases successively.
[0012] Preferably, each of the several layers of material contains only one kind of ceramic powder; or n-1 layers of material in the several layers of material contain two kinds of ceramic powders, and the remaining layer of material contains one or two kinds of ceramic powders, where n is the number of material layers, and n≥2;
[0013] When each of the several layers of materials contains only one type of ceramic powder:
[0014] The refractive index of the ceramic powder in each layer of material is independently 1.3 to 1.7;
[0015] Taking the material layer with the darkest color as the top layer, the absolute value of the difference between the refractive index of the ceramic powder and the refractive index of the resin in each layer of material decreases from top to bottom;
[0016] When n-1 layers of the plurality of material layers contain two kinds of ceramic powders, and the remaining layer of material contains one or two kinds of ceramic powders:
[0017] The two ceramic powders are a first ceramic powder and a second ceramic powder; the refractive index of the first ceramic powder is 1.3 to 1.7; the refractive index of the second ceramic powder is 1.3 to 2.5;
[0018] When the refractive index of the second ceramic powder is 1.3-1.7, the ceramic powder accounts for ≥50% by weight of the ceramic powder in each layer, and the ceramic powder is used as the main powder, and the other is used as the secondary powder;
[0019] When the refractive index of the second ceramic powder is greater than 1.7 and less than or equal to 2.5, the mass proportion of the first ceramic powder in the ceramic powder in each layer of material is greater than or equal to 33%; the first ceramic powder is used as the main powder and the second ceramic powder is used as the secondary powder;
[0020] The material layer with the darkest color is taken as the uppermost layer, and from top to bottom, the mass ratio of the main powder to the secondary powder in the several layers of materials increases successively.
[0021] Preferably, when each of the several layers of materials contains only one type of ceramic powder, the particle size D50 of the ceramic powder in each layer of material is independently 50 nm to 60 μm.
[0022] Preferably, the particle size D50 of the primary powder is 50 nm to 60 μm; the particle size D50 of the secondary powder is 10 nm to 30 μm.
[0023] Preferably, the absolute value of the difference in mass percentage of the colorant in two adjacent layers of the plurality of layers of material is ≤15%.
[0024] Preferably, the absolute value of the difference in mass percentage of the main powder and the absolute value of the difference in mass percentage of the secondary powder in two adjacent layers of materials are both ≤20%.
[0025] Preferably, the first ceramic powder includes one of feldspar, nepheline, quartz, sodium aluminum silicate, hydroxyapatite, fluoroapatite, glass ceramics and porcelain powder;
[0026] The second ceramic powder includes one of feldspar, nepheline, quartz, sodium aluminum silicate, hydroxyapatite, fluoroapatite, glass ceramics, porcelain powder, metal oxide, metal sulfate and metal carbonate.
[0027] Preferably, the feldspar includes one of potassium feldspar, sodium feldspar, calcium feldspar, orthoclase, microcline and sanudite;
[0028] The glass ceramics include one of borosilicate glass, aluminosilicate glass and fluoroaluminosilicate glass;
[0029] Porcelain powder includes leucite glass-ceramic powder or feldspar porcelain powder;
[0030] The metal oxide includes one or more of zinc oxide, calcium oxide, magnesium oxide, aluminum oxide, yttrium oxide, zirconium oxide, titanium dioxide, cerium dioxide and niobium oxide;
[0031] The metal sulfate includes calcium sulfate or aluminum sulfate;
[0032] The metal carbonate includes calcium carbonate.
[0033] Preferably, the colorant includes one or more of ferrozirconium red, chrome tin red, ferrosilicon red, iron red, cobalt black, iron black, vanadium yellow, zirconium spectrum yellow, vanadium tin yellow, orange yellow and iron yellow.
[0034] Preferably, the toughening agent comprises inorganic fibers.
[0035] Preferably, the number of layers of the material is more than 3; taking the total mass of all layers of material as 100%, the mass proportions of the topmost layer of material and the bottommost layer of material are independently 16-50%, and the mass proportions of the middle layers of material are independently 10-35%.
[0036] Preferably, the porosity of the porous ceramic skeleton is 10-60%.
[0037] Preferably, in terms of mass percentage, the raw materials for preparing the resin include 97-99.9% of monomers and 0.1-3% of initiators; the refractive index of the resin is 1.4-1.7.
[0038] Preferably, the monomers include a main monomer and a diluent monomer; the mass ratio of the main monomer to the diluent monomer is 0.5 to 9:1;
[0039] The main monomer is one or more of bisphenol A glycidyl methacrylate, ethoxylated bisphenol A dimethacrylate and urethane dimethacrylate;
[0040] The diluent monomer includes one or more of triethylene glycol dimethacrylate, ethylene glycol dimethacrylate and trimethylolpropane triacrylate.
[0041] Preferably, the initiator comprises a thermal initiator and / or a photoinitiator.
[0042] The present invention provides a method for preparing the resin-infiltrated ceramic composite material described in the above scheme, comprising the following steps: immersing a porous ceramic skeleton into a resin raw material for vacuum infiltration, and curing the resin raw material after it infiltrates into the porous ceramic skeleton to obtain the resin-infiltrated ceramic composite material.
[0043] Preferably, the method for preparing the porous ceramic skeleton comprises the following steps:
[0044] The colorant, toughening agent and ceramic powder are mixed according to the proportion to obtain materials for each layer;
[0045] The materials of each layer are stacked and laid flat, and then pressed into shape to obtain a green body;
[0046] The green body is sintered to obtain the porous ceramic skeleton.
[0047] Preferably, before the vacuum infiltration, coupling modification of the porous ceramic skeleton is also included.
[0048] Preferably, the press forming comprises sequentially performing dry pressing and cold isostatic pressing;
[0049] The dry pressing pressure is 1 to 20 MPa;
[0050] The cold isostatic pressing pressure is 100-300 MPa.
[0051] Preferably, the sintering temperature is 700-1600°C
[0052] The present invention provides the use of the resin-infiltrated ceramic composite material described in the above scheme or the resin-infiltrated ceramic composite material prepared by the preparation method described in the above scheme in preparing dental restorations.
[0053] The present invention provides a resin-infiltrated ceramic composite material, which consists of a multilayer structure, each layer including a porous ceramic skeleton and a resin infiltrated in the pore structure of the porous ceramic skeleton; from top to bottom, the light transmittance of each layer of the resin-infiltrated ceramic composite material increases successively, the absolute value of the difference in light transmittance between two adjacent layers is 0.5-10%, and the absolute value of the difference in light transmittance between the uppermost layer and the lowermost layer is greater than 3%; from top to bottom, the color of each layer of the resin-infiltrated ceramic composite material becomes lighter successively, the color difference between two adjacent layers is 0.5-11, and the color difference between the uppermost layer and the lowermost layer is 1-30. The resin-infiltrated ceramic composite material provided by the present invention has the effect of gradual change of light transmittance and color from the incision end to the neck, and the transition is natural, and the aesthetic restoration effect is good.
[0054] The present invention provides a method for preparing the resin-infiltrated ceramic composite material described in the above scheme, wherein the porous ceramic skeleton is obtained by sintering several layers of material after being pressed and formed, wherein each layer of the several layers of material contains only one kind of ceramic powder, or n-1 layers of the several layers of material contain two kinds of ceramic powders, and the remaining layer of material contains one or two kinds of ceramic powders; when each layer of material contains only one kind of ceramic powder, the present invention achieves a gradual change in transmittance by controlling the absolute value of the difference between the refractive index of the ceramic powder in each layer of material and the refractive index of the resin to be filled to decrease in sequence;
[0055] When n-1 layers of material contain 2 kinds of ceramic powders and the remaining layer of material contains 1 or 2 kinds of ceramic powders, the present invention divides the ceramic powder into a main powder and a secondary powder, and the refractive index of the main powder is close to the refractive index of the resin to be filled (the refractive index of the resin is generally 1.4-1.7), so as to ensure that the cut end of the formed resin-infiltrated ceramic composite material has a higher transmittance; the effect of gradual change in transmittance is achieved by adding the secondary powder. Specifically, the greater the difference in refractive index between the secondary powder and the main powder, the more severe the scattering of light inside the material and the lower the transmittance of the material. The present invention controls the proportion of the main powder and the secondary powder in each layer of material to achieve the effect of gradual change in transmittance.
[0056] In addition, the present invention achieves a color gradient effect from the cut end to the neck by controlling the proportion of colorant in each layer of material; and by controlling the particle size of the ceramic powder, the transition of each layer is natural, which greatly improves the aesthetic performance of the resin-infiltrated ceramic composite material.
[0057] The resin-infiltrated ceramic composite material of the present invention is used for aesthetic restoration of veneers or anterior tooth single crowns, etc., and has a good aesthetic restoration effect. DETAILED DESCRIPTION
[0058] The present invention provides a resin-infiltrated ceramic composite material, which is composed of a multi-layer structure, each layer including a porous ceramic skeleton and a resin infiltrated in the pore structure of the porous ceramic skeleton;
[0059] From top to bottom, the light transmittance of each layer of the resin-infiltrated ceramic composite material increases successively, the absolute value of the difference in light transmittance between two adjacent layers is 0.5-10%, and the absolute value of the difference in light transmittance between the uppermost layer and the lowermost layer is greater than 3%;
[0060] From top to bottom, the colors of the layers of the resin-infiltrated ceramic composite material gradually become lighter, the color difference between two adjacent layers is 0.5-11, and the color difference between the uppermost layer and the lowermost layer is 1-30.
[0061] In a specific embodiment, the absolute value of the difference in light transmittance between two adjacent layers of the resin-infiltrated ceramic composite material can be 0.5%, 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. The absolute value of the difference in light transmittance between the uppermost layer and the lowermost layer of the resin-infiltrated ceramic composite material is greater than 3%, and there is no upper limit requirement; in a specific embodiment, the absolute value of the difference in light transmittance between the uppermost layer and the lowermost layer of the resin-infiltrated ceramic composite material can be 3%, 5%, 7%, 10%, 12%, 15%, 17%, 19% or 20%. In the present invention, the light transmittance (also called linear transmittance) is obtained by testing according to standard GB / T2410-2008.
[0062] In a specific embodiment, the color difference between two adjacent layers of the resin-infiltrated ceramic composite material can be 0.5, 1, 1.5, 2, 2.5, 3, 4, 5, 6, 7, 8, 9, 10 or 11; the color difference between the top layer and the bottom layer of the resin-infiltrated ceramic composite material can be 1, 5, 10, 15, 20, 25 or 30.
[0063] In the present invention, the resin-infiltrated ceramic composite material has a gradual effect of gradually decreasing light transmittance and gradually deepening color from the cut end to the neck, and the transition is natural.
[0064] Next, the resin will be described.
[0065] In the present invention, the refractive index of the resin is 1.4 to 1.7; in a specific embodiment, the refractive index of the resin is 1.4, 1.5, 1.6 or 1.7.
[0066] In terms of mass percentage, the raw materials for preparing the resin preferably include 97-99.9% monomer and 0.1-3% initiator; in a specific embodiment, the mass content of the monomer can be 97%, 97.5%, 98%, 99%, 99.5% or 99.9%.
[0067] In the present invention, the monomer preferably includes a main monomer and a diluent monomer; the mass ratio of the main monomer to the diluent monomer is preferably 0.5 to 9:1. In a specific embodiment, the mass ratio of the main monomer to the diluent monomer can be 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 7:1 or 9:1.
[0068] In the present invention, the main monomer preferably includes one or more of bisphenol A glycidyl methacrylate (Bis-GMA), ethoxylated bisphenol A dimethacrylate (Bis-MEPP) and urethane dimethacrylate (UDMA).
[0069] In the present invention, the diluent monomer preferably includes one or more of triethylene glycol dimethacrylate (TEGDMA), ethylene glycol dimethacrylate (EGDMA) and trimethylolpropane triacrylate (TMPTMA).
[0070] In the present invention, the initiator preferably includes a thermal initiator and / or a photoinitiator, and the thermal initiator preferably includes one or more of benzoyl peroxide (BPO), tert-butyl peracetate, diisopropylbenzene peroxide (DCP), tert-butyl peroxy-2-ethylhexanoate (TBPO) and tert-butyl peroxybenzoate (CP-01); the photoinitiator preferably includes one or more of camphorquinone (CQ), di(2,4,6-trimethylbenzoyl)phenylphosphine oxide (TPO) and ethyl 2,4,6-trimethylbenzoylphenylphosphonate (TPO-L).
[0071] The porous ceramic skeleton is described below.
[0072] In the present invention, the porous ceramic skeleton is preferably obtained by molding several layers of materials and then sintering them.
[0073] In terms of percentage by mass, each layer of material independently comprises 0-30% of a colorant, 0-20% of a toughening agent, and the remainder of ceramic powder; and the material layer with the darkest color is the uppermost layer, and from top to bottom, the mass percentage of the colorant in the several layers of material decreases in sequence;
[0074] Each of the several layers of materials contains only one type of ceramic powder; or n-1 layers of materials in the several layers of materials contain two types of ceramic powders, and the remaining layer of materials contains one or two types of ceramic powders, where n is the number of material layers, and n≥2;
[0075] When each of the several layers of materials contains only one type of ceramic powder:
[0076] The refractive index of the ceramic powder in each layer of material is independently 1.3 to 1.7, and the particle size D50 is independently 50 nm to 60 μm;
[0077] The material layer with the darkest color is taken as the uppermost layer, and from top to bottom, the absolute value of the difference between the refractive index of the ceramic powder and the refractive index of the resin in each layer of material decreases successively; the refractive index of the resin is 1.4 to 1.7;
[0078] When n-1 layers of the plurality of material layers contain two kinds of ceramic powders, and the remaining layer of material contains one or two kinds of ceramic powders:
[0079] The two ceramic powders are a first ceramic powder and a second ceramic powder; the refractive index of the first ceramic powder is 1.3 to 1.7; the refractive index of the second ceramic powder is 1.3 to 2.5;
[0080] When the refractive index of the second ceramic powder is 1.3-1.7, the ceramic powder accounts for ≥50% by weight of the ceramic powder in each layer, and the ceramic powder is used as the main powder, and the other is used as the secondary powder;
[0081] When the refractive index of the second ceramic powder is greater than 1.7 and less than or equal to 2.5, the mass proportion of the first ceramic powder in the ceramic powder in each layer of material is greater than or equal to 33%; the first ceramic powder is used as the main powder and the second ceramic powder is used as the secondary powder;
[0082] The material layer with the darkest color is taken as the uppermost layer, and from top to bottom, the mass ratio of the main powder to the secondary powder in the several layers of materials increases successively;
[0083] The particle size D50 of the main powder is 50nm-60μm; the particle size D50 of the secondary powder is 10nm-30μm.
[0084] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.
[0085] In the present invention, each layer of material independently includes 0 to 30% of colorant in terms of mass percentage; in a specific embodiment, the mass percentage of the colorant can be 0%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 24%, 26% or 30%. In the present invention, the colorant preferably includes one or more of zirconium iron red, chrome tin red, silicon iron red, iron red, cobalt black, iron black, vanadium yellow, zirconium spectrum yellow, vanadium tin yellow, orange yellow and iron yellow. In the present invention, the type of colorant in each layer of material is preferably the same. In the present invention, the material layer with the darkest color is taken as the top layer, and from top to bottom, the mass percentage of the colorant in the several layers of material decreases successively, and more preferably, the absolute value of the difference in the mass percentage of the colorant in two adjacent layers of material is ≤15%, more preferably ≤10%, and further preferably 1 to 5%. The present invention achieves the effect of gradually lightening the color from the neck to the cut end by controlling the mass percentage of the colorant to decrease successively. In addition, the present invention controls the mass proportion of the colorant to be below 30%, which can prevent the colorant content from being too high and excessively reducing the transmittance.
[0086] In the present invention, each layer of material independently includes 0 to 20% of a toughening agent in terms of mass percentage; in a specific embodiment, the mass percentage of the toughening agent may be 0%, 5%, 10%, 13%, 15%, 17% or 20%. In the present invention, the toughening agent preferably includes inorganic fibers; the inorganic fibers preferably include one or more of glass fibers, silica fibers, silicon carbide fibers, alumina fibers and aluminum silicate fibers. In the present invention, the mass percentage of the toughening agent in each layer of material may be the same or different, preferably the same; the types of toughening agents in each layer of material may be the same or different, preferably the same. The present invention can improve the hardness and wear resistance of the resin-infiltrated ceramic composite material by adding a toughening agent.
[0087] In the present invention, each layer of material also includes a surplus of ceramic powder.
[0088] In the present invention, each layer of material contains only one kind of ceramic powder (in this case, the types of ceramic powders in each layer of material are different); or there are n-1 layers of material containing two kinds of ceramic powders, and the remaining layer of material contains one or two kinds of ceramic powders (the types of the two ceramic powders in each layer of material are the same), n is the number of material layers, n≥2.
[0089] In the present invention, when each layer of material contains only one kind of ceramic powder, the refractive index of the ceramic powder in each layer of material is independently 1.3 to 1.7; in a specific embodiment, the refractive index of the ceramic powder can be 1.3, 1.4, 1.5, 1.6 or 1.7. The refractive index of the resin in the conventional resin-infiltrated ceramic composite material is 1.4 to 1.7, and the refractive index of the ceramic powder is close to the refractive index of the resin to be filled, which can ensure that the cut end of the formed resin-infiltrated ceramic composite material has a high degree of transparency. In the present invention, the particle size D50 of the ceramic powder in each layer of material is independently 50nm to 60μm; in a specific embodiment, the particle size D50 of the ceramic powder can be 50nm, 1μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm or 60μm. The present invention controls the particle size of the ceramic powder within the above range, which can prevent the particle size from being too large, resulting in unnatural transitions between layers, and prevent the hardness and wear resistance from being reduced.
[0090] In the present invention, the ceramic powder preferably includes one of feldspar, nepheline, quartz, sodium aluminum silicate, hydroxyapatite, fluoroapatite, glass ceramics and porcelain powder; wherein the feldspar preferably includes one of potassium feldspar, sodium feldspar, calcium feldspar, orthoclase, microcline and sanidine; the glass ceramic preferably includes one of borosilicate glass, aluminosilicate glass and fluoroaluminosilicate glass; the porcelain powder preferably includes white garnet microcrystalline glass powder or feldspar porcelain powder.
[0091] In the present invention, the material layer with the darkest color is taken as the uppermost layer, and from top to bottom, the absolute value of the difference between the refractive index of the ceramic powder in each material layer and the refractive index of the resin to be filled decreases successively. In a specific embodiment, when the number of material layers is 6, from top to bottom, the absolute value of the difference between the refractive index of the ceramic powder and the resin in each material layer is 0.12, 0.6, 0.5, 0.3, 0.2 and 0 successively. The present invention achieves the effect of gradual change of light transmittance by controlling the absolute value of the difference between the refractive index of the ceramic powder and the refractive index of the resin in each material layer to decrease successively.
[0092] In the present invention, when n-1 layers of materials contain two kinds of ceramic powders and the remaining layer of materials contains one or two kinds of ceramic powders, the ceramic powders are divided into first ceramic powders and second ceramic powders.
[0093] In the present invention, the refractive index of the first ceramic powder is 1.3-1.7. In a specific embodiment, the refractive index of the first ceramic powder may be 1.3, 1.4, 1.5, 1.6 or 1.7; the refractive index of the second ceramic powder is 1.3-2.5. In a specific embodiment, the refractive index of the second ceramic powder may be 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4 or 2.5.
[0094] In the present invention, the first ceramic powder preferably includes one of feldspar, nepheline, quartz, sodium aluminum silicate, hydroxyapatite, glass ceramics and porcelain powder; wherein the feldspar preferably includes one of potassium feldspar, sodium feldspar, calcium feldspar, orthoclase, microcline and sanidine; the glass ceramic preferably includes one of borosilicate glass, aluminosilicate glass and fluoroaluminosilicate glass; the porcelain powder preferably includes white garnet microcrystalline glass powder or feldspar porcelain powder.
[0095] In the present invention, in addition to being the types listed for the first ceramic powder, the second ceramic powder may also be one of metal oxides, metal sulfates and metal carbonates; the metal oxide preferably includes one of zinc oxide, calcium oxide, magnesium oxide, aluminum oxide, yttrium oxide, zirconium oxide, titanium dioxide, cerium dioxide and niobium oxide; the metal sulfate preferably includes calcium sulfate or aluminum sulfate; the metal carbonate preferably includes calcium carbonate.
[0096] In the present invention, when the refractive index of the second ceramic powder is 1.3-1.7, the ceramic powder of each layer accounts for ≥50% by mass of the same ceramic powder, and the ceramic powder is used as the main powder and the other is used as the secondary powder.
[0097] When the refractive index of the second ceramic powder is greater than 1.7 and less than or equal to 2.5, the mass proportion of the first ceramic powder in the ceramic powder in each layer of material is always ≥ 33%; at this time, the first ceramic powder is used as the main powder and the second ceramic powder is used as the secondary powder.
[0098] In the present invention, the particle size D50 of the main powder is 50nm to 60μm; in a specific embodiment, the particle size D50 of the main powder can be 50nm, 1μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm or 60μm. The present invention controls the particle size of the main powder within the above range to prevent the unnatural transition of each layer caused by too large a particle size.
[0099] In the present invention, the particle size D50 of the secondary powder is 10nm to 30μm; in a specific embodiment, the particle size D50 of the secondary powder can be 10nm, 100nm, 1μm, 5μm, 10μm, 15μm, 20μm, 25μm or 30μm. The present invention controls the particle size of the secondary powder within the above range to prevent the particle size from being too large, resulting in unnatural transitions between layers.
[0100] In the present invention, the greater the difference in refractive index between the primary powder and the secondary powder, the more severe the scattering of light inside the material and the lower the transparency of the material.
[0101] The material layer with the darkest color is taken as the uppermost layer, and from top to bottom, the mass ratio of the main powder to the secondary powder in the several layers of materials increases successively.
[0102] More preferably, when n-1 layers of material among the several layers of material contain 2 kinds of ceramic powders and the remaining layer of material contains 1 or 2 kinds of ceramic powders, the absolute value of the difference in the mass proportion of the main powder in two adjacent layers of material and the absolute value of the difference in the mass proportion of the secondary powder are preferably ≤20%.
[0103] In a specific embodiment, when the number of material layers is 3, from the neck layer to the cut end layer, the mass ratio of the main powder to the secondary powder can be 1.7, 2.5 and 5.0 respectively; when the number of material layers is 5, from the neck layer to the cut end layer, the mass ratio of the main powder to the secondary powder can be 1.7, 2.5, 5.0, 6.7 and 20.0 respectively, or the mass ratio of the main powder to the secondary powder can be 1.3, 1.4, 1.5, 1.7, 2.0 respectively; when the number of material layers is 6, from the neck layer to the cut end layer, the mass ratio of the main powder to the secondary powder can be 1.0, 1.2, 1.7, 2.5, 5.0 and infinity respectively.
[0104] The refractive index of the resin in conventional resin-infiltrated ceramic composite materials is 1.4 to 1.7. The present invention always uses ceramic powder with a refractive index of 1.3 to 1.7 as the main powder. The refractive index of the main powder is close to the refractive index of the resin to be filled, which can ensure that the cut end of the formed resin-infiltrated ceramic composite material has a high degree of transparency. In the present invention, the greater the difference in refractive index between the secondary powder and the main powder, the more serious the scattering of light inside the material, and the lower the transparency of the material. The present invention controls the proportion of the main powder and the secondary powder in each layer of the material to achieve a gradual effect of light transmittance.
[0105] In the present invention, the number of layers of the material is preferably 3 or more, more preferably 3 to 8 layers, and in a specific embodiment, it can be 3, 4, 5, 6, 7 or 8 layers. Taking the total mass of all layers of material as 100%, the mass proportion of the uppermost layer of material and the lowermost layer of material is independently preferably 16 to 50%, and more preferably the mass proportion of the uppermost layer of material and the lowermost layer of material is the same; the mass proportion of the middle layers of material can also be the same or different, preferably 10 to 35%. In the present invention, the mass proportion of the middle layers of material is the same, which is conducive to achieving a natural transition effect.
[0106] In a specific embodiment of the present invention, the mass proportion of the topmost material layer (neck layer) and the bottommost material layer (cut end layer) can be 16%, 20%, 25%, 30%, 35%, 40%, 45% or 50%; the mass proportion of the middle layers of material can be 10%, 15%, 20%, 25% or 30%.
[0107] In the present invention, the porosity of the porous ceramic skeleton is preferably 10-60%; in a specific embodiment, the porosity of the porous ceramic skeleton may be 10%, 20%, 30%, 40%, 50% or 60%.
[0108] The present invention provides a method for preparing the resin-infiltrated ceramic composite material described in the above scheme, comprising the following steps: immersing a porous ceramic skeleton into a resin raw material for vacuum infiltration, and curing the resin raw material after it infiltrates into the porous ceramic skeleton to obtain the resin-infiltrated ceramic composite material.
[0109] In the present invention, the method for preparing the porous ceramic skeleton preferably comprises the following steps: mixing a colorant, a toughening agent and a ceramic powder according to a ratio to obtain materials for each layer;
[0110] The materials of each layer are stacked and laid flat, and then pressed into shape to obtain a green body;
[0111] The green body is sintered to obtain the porous ceramic skeleton.
[0112] The present invention mixes various materials according to a proportion to obtain materials of various layers.
[0113] Before the mixing, the present invention preferably granulates the ceramic powder; the present invention has no special requirements for the granulation process, and a granulation process well known in the art can be used, such as adding an appropriate amount of polyvinyl alcohol as a binder for granulation. The present invention has no special requirements for the mixing, and it only needs to be able to mix the materials evenly.
[0114] After obtaining each layer of material, the present invention stacks and lays each layer of material flat and then presses and forms the material to obtain a green body.
[0115] When paving, the present invention lays the materials in order according to the composition of each layer and the mass proportion of each layer.
[0116] In the present invention, the pressing preferably includes dry pressing and cold isostatic pressing in sequence; the pressure of the dry pressing is preferably 1-20 MPa, and the present invention has no special requirements for the time of the dry pressing, as long as it can be formed; the pressure of the cold isostatic pressing is preferably 100-300 MPa, and the holding time is preferably 0.5-30 min. In a specific embodiment, the pressure of the dry pressing can be 1 MPa, 5 MPa, 10 MPa, 15 MPa or 20 MPa; the pressure of the cold isostatic pressing can be 100 MPa, 150 MPa, 200 MPa, 250 MPa or 300 MPa, and the time of the cold isostatic pressing can be 0.5 min, 5 min, 10 min, 15 min, 20 min, 25 min or 30 min.
[0117] After obtaining the green body, the present invention sintered the green body to obtain the porous ceramic skeleton.
[0118] In the present invention, the sintering temperature is preferably 700-1600°C; the sintering holding time is preferably 0.5-24h; the sintering is preferably carried out in an air atmosphere; in a specific embodiment, the sintering temperature can be 700°C, 800°C, 1000°C, 1200°C, 1400°C, 1500°C or 1600°C; the sintering time can be 0.5h, 5h, 8h, 10h, 15h, 18h, 20h or 24h.
[0119] Before the impregnation, the present invention preferably first performs coupling modification on the porous ceramic skeleton; the present invention has no special requirements for the coupling modification method, and a coupling modification method well known in the art can be used, for example: water, ethanol, acetic acid and a coupling agent are mixed to obtain a modified liquid; the porous ceramic skeleton is placed in the modified liquid, and vacuuming, pressure maintaining and drying are performed in sequence to obtain a coupled modified porous ceramic skeleton. The present invention does not further elaborate on the specific conditions of the coupling modification, which is common knowledge in the art.
[0120] In the present invention, the coupling agent used for the coupling modification is preferably a silane coupling agent; the silane coupling agent includes one or more of vinyl trimethoxysilane, vinyl triethoxysilane, vinyl trichlorosilane, vinyl tri(β-methoxyethoxy) silane, γ-methacryloxypropyl trimethoxysilane, 11-methacryloxy undecyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane and γ-aminopropyl triethoxysilane, more preferably γ-methacryloxypropyl trimethoxysilane (KH570).
[0121] The present invention improves the bonding force between the porous ceramic skeleton and the resin through coupling modification.
[0122] In the present invention, the resin raw material is preferably obtained by mixing various raw materials for preparing the resin and then degassing them under vacuum. In the present invention, the raw materials for preparing the resin are preferably mixed under water bath heating and stirring conditions; the temperature of the water bath heating is preferably 45° C.; the present invention has no special requirements for the stirring rate and time, as long as the various raw materials can be mixed evenly. The present invention has no special requirements for the conditions for vacuum degassing.
[0123] In the present invention, the pressure of the vacuum penetration is preferably -0.1 to 0 MPa, and the time of the vacuum penetration is preferably 8 to 240 h, more preferably 50 to 200 h, and further preferably 100 to 168 h.
[0124] In the present invention, the curing preferably comprises:
[0125] In the present invention, the curing pressure is preferably 50-350MPa; the maximum curing temperature is preferably 80-150°C; and the holding time at the maximum temperature is preferably 2-12h. In a specific embodiment, the curing pressure can be 50MPa, 100MPa, 150MPa, 200MPa, 250MPa, 300MPa or 350MPa; the maximum curing temperature can be 80°C, 100°C, 120°C, 130°C or 150°C; and the holding time at the maximum temperature can be 2h, 4h, 6h, 8h, 10h or 12h.
[0126] In the present invention, the infiltrated resin ceramic is preferably placed at 70°C and a curing pressure for 5 to 6 hours and then heated to the highest curing temperature for heat preservation. The heating rate is preferably 2 to 5°C / min.
[0127] The present invention provides the use of the resin-infiltrated ceramic composite material in preparing a dental restoration. The present invention has no special requirements on the type of the dental restoration, and any dental restoration known in the art can be used, such as veneers and anterior single crowns.
[0128] The porous ceramic skeleton and its preparation method, the resin-infiltrated ceramic composite material and its preparation method and application provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0129] Example 1
[0130] The porous ceramic skeleton is composed of feldspar (main powder, specifically potassium feldspar), sodium aluminum silicate (secondary powder) and colorants (specific types are zircon red, vanadium yellow and cobalt black), wherein the refractive index of feldspar is 1.51, the particle size D50 is 1.5 μm, the refractive index of sodium aluminum silicate is 1.54, the particle size D50 is 1 μm, the total mass of each layer is 100%, the total number of layers is 6, and the specific composition is shown in Table 1;
[0131] The porous ceramic skeleton preparation method is as follows:
[0132] (1) Ingredients
[0133] After the granulated feldspar, the granulated sodium aluminum silicate powder and the colorant are uniformly mixed according to the mass ratio, the mixture is laid flat in the mold cavity according to the neck layer, the middle layer A, the middle layer B, the middle layer C, the middle layer D and the cut end layer;
[0134] (2) Molding
[0135] The cavity material is dry pressed at 10 MPa, and then cold isostatically pressed at 200 MPa for 1 min to obtain a green body;
[0136] (3) Sintering
[0137] The green body was placed in a sintering furnace and sintered at 1000° C. to obtain a porous ceramic skeleton with a porosity of 30%.
[0138] Example 2
[0139] The porous ceramic skeleton is composed of feldspar (main powder, specifically albite), silicon dioxide (secondary powder) and colorants (specifically chrome tin red, zirconium spectrum yellow and cobalt black), wherein the refractive index of feldspar is 1.51, the particle size D50 is 3.5 μm, the refractive index of silicon dioxide is 1.46, the particle size D50 is 0.5 μm, the total mass of each layer is 100%, the total number of layers is 5, and the specific composition is shown in Table 1;
[0140] The preparation method is as follows:
[0141] (1) Ingredients
[0142] The batching method is the same as in Example 1;
[0143] (2) Molding
[0144] The cavity material is dry pressed at 10 MPa, and then cold isostatically pressed at 200 MPa for 1 min to obtain a green body;
[0145] (3) Sintering
[0146] The green body was placed in a sintering furnace and sintered at 1200° C. to obtain a porous ceramic skeleton with a porosity of 35%.
[0147] Example 3
[0148] The porous ceramic skeleton is composed of borosilicate glass (main powder), silicon dioxide (secondary powder) and colorants (specific types are ferrosilicon red, vanadium tin yellow and cobalt black), wherein the refractive index of the borosilicate glass is 1.48, the particle size D50 is 8.9 μm, the refractive index of silicon dioxide is 1.46, the particle size D50 is 7.0 μm, the total mass of each layer is 100%, the total number of layers is 5, and the specific composition is shown in Table 1;
[0149] The preparation method is as follows:
[0150] (1) Ingredients
[0151] The batching method is the same as in Example 1;
[0152] (2) Molding
[0153] The cavity material is dry pressed at 10 MPa, and then cold isostatically pressed at 250 MPa for 1 min to obtain a green body;
[0154] (3) Sintering
[0155] The green body was placed in a sintering furnace and sintered at 750° C. to obtain a porous ceramic skeleton with a porosity of 45%.
[0156] Example 4
[0157] The porous ceramic skeleton is composed of aluminosilicate glass (main powder), zirconium oxide (secondary powder) and colorants (specific types are ferrosilicon red, vanadium tin yellow and cobalt black), wherein the refractive index of the aluminosilicate glass is 1.53, the particle size D50 is 13 μm, the refractive index of the zirconium oxide is 2.2, the particle size D50 is 22.8 nm, the total mass of each layer is 100%, the total number of layers is 5, and the specific composition is shown in Table 1;
[0158] The preparation method is as follows:
[0159] (1) Ingredients
[0160] The batching method is the same as in Example 1;
[0161] (2) Molding
[0162] The cavity material is dry pressed at 10 MPa, and then cold isostatically pressed at 220 MPa for 1 min to obtain a green body;
[0163] (3) Sintering
[0164] The green body was placed in a sintering furnace and sintered at 750° C. to obtain a porous ceramic skeleton with a porosity of 37%.
[0165] Example 5
[0166] The porous ceramic skeleton is composed of leucite glass-ceramics (main powder), hydroxyapatite (secondary powder) and colorants (specific types are zircon red, iron yellow and cobalt black), wherein the refractive index of leucite glass-ceramics is 1.49, the particle size D50 is 5 μm, the refractive index of hydroxyapatite is 1.6, the particle size D50 is 5.7 μm, the total mass of each layer is 100%, the total number of layers is 3, and the specific composition is shown in Table 1;
[0167] The preparation method is as follows:
[0168] (1) Ingredients
[0169] The batching method is the same as in Example 1;
[0170] (2) Molding
[0171] The cavity material was dry pressed at 10 MPa, and then cold isostatic pressed at 290 MPa for 1 min to obtain a green body;
[0172] (3) Sintering
[0173] The green body was placed in a sintering furnace and sintered at 780° C. to obtain a porous ceramic skeleton with a porosity of 32%.
[0174] Example 6
[0175] The total mass of each layer of the porous ceramic skeleton is 100%. From the neck layer to the middle layer and then to the cut end layer, the refractive index of the ceramic powder in each layer decreases successively, and the refractive index difference with the resin to be filled decreases successively, and the linear transmittance of the material gradually increases. The specific composition is as follows:
[0176] (1) The neck layer is composed of 75% hydroxyapatite (refractive index 1.60) and 25% colorant (specifically composed of zirconium iron red, iron yellow and cobalt black), of which the particle size D50 of hydroxyapatite is 5.7 μm, and this layer accounts for 20%;
[0177] (2) The middle A layer is composed of 77% sodium aluminum silicate (refractive index 1.54) and 23% colorant, of which the particle size D50 of sodium aluminum silicate is 8.7 μm and the proportion of this layer is 15%;
[0178] (3) The middle B layer is composed of 79% aluminosilicate glass (refractive index 1.53) and 21% colorant, where the particle size D50 of the aluminosilicate glass is 4.5 μm, and this layer accounts for 15%;
[0179] (4) The middle C layer is composed of 82% feldspar (refractive index 1.51) and 18% colorant, of which the particle size D50 of feldspar is 10.5 μm, and this layer accounts for 15%;
[0180] (5) The middle D layer is composed of 85% silica (refractive index 1.46) and 15% colorant, where the particle size D50 of silica is 25.3 μm, and this layer accounts for 15%;
[0181] (6) The cut end layer is composed of 87% borosilicate glass (refractive index 1.48) and 13% colorant, where the particle size D50 of the borosilicate glass is 9.5 μm, and this layer accounts for 20%;
[0182] The preparation method is as follows:
[0183] (1) Ingredients
[0184] The batching method is the same as in Example 1;
[0185] (2) Molding
[0186] The cavity material is dry pressed at 10 MPa, and then cold isostatically pressed at 250 MPa for 1 min to obtain a green body;
[0187] (3) Sintering
[0188] The green body was placed in a sintering furnace and sintered at 880° C. for 120 min to obtain a porous ceramic skeleton with a porosity of 37%.
[0189] Example 7
[0190] The porous ceramic skeleton is composed of feldspar (main powder, specifically albite), silicon dioxide (secondary powder), colorant (specifically chrome tin red, zirconium spectrum yellow and cobalt black), and toughening agent (specifically silicon carbide fiber), wherein the refractive index of feldspar is 1.51, the particle size D50 is 3.5 μm, the refractive index of silicon dioxide is 1.46, the particle size D50 is 0.5 μm, the total mass of each layer is 100%, the total number of layers is 5, and the specific composition is as follows:
[0191] (1) The neck layer is composed of 53.81% feldspar, 31.66% silica, 10.00% colorant and 4.53 toughening agent, accounting for 35%;
[0192] (2) The middle A layer is composed of 59.13% feldspar, 23.67% silica, 8.00% colorant and 9.20% toughening agent, accounting for 10%;
[0193] (3) The middle B layer is composed of 70.50% feldspar, 14.10% silica, 6.00% colorant and 9.40% toughening agent, accounting for 10%;
[0194] (4) The middle C layer is composed of 71.37% feldspar, 10.70% silica, 4.00% colorant and 13.93% toughening agent, accounting for 10%;
[0195] (5) The cut end layer is composed of 83.47% feldspar, 4.17% silica, 3.00% colorant and 9.36% toughening agent, accounting for 35%;
[0196] The preparation method is as follows:
[0197] (1) Ingredients
[0198] The batching method is the same as in Example 1;
[0199] (2) Molding
[0200] The cavity material is dry pressed at 10 MPa, and then cold isostatically pressed at 200 MPa for 1 min to obtain a green body;
[0201] (3) Sintering
[0202] The green body was placed in a sintering furnace and sintered at 1200° C. for 180 min to obtain a porous ceramic skeleton with a porosity of 35%.
[0203] Comparative Example 1
[0204] The porous ceramic skeleton is composed of feldspar (specifically potassium feldspar), sodium aluminum silicate and colorants (specifically zirconium iron red, vanadium yellow and cobalt black), wherein the refractive index of feldspar is 1.51, the particle size D50 is 1.5 μm, the refractive index of sodium aluminum silicate is 1.54, the particle size D50 is 1 μm, the total mass of each layer is 100%, the total number of layers is 6, and the specific composition is shown in Table 1;
[0205] The preparation method is as follows:
[0206] (1) Ingredients
[0207] Same as Example 1;
[0208] (2) Molding
[0209] The cavity material is dry pressed at 10 MPa, and then cold isostatically pressed at 200 MPa for 1 min to obtain a green body;
[0210] (3) Sintering
[0211] The green body was placed in a sintering furnace and sintered at 1000° C. for 120 min to obtain a porous ceramic skeleton with a porosity of 30%.
[0212] Comparative Example 2
[0213] The porous ceramic skeleton is composed of feldspar (specifically microcline, main powder), silicon dioxide (secondary powder) and colorant (specifically zircon red, iron yellow and cobalt black), wherein the refractive index of feldspar is 1.51, the particle size D50 is 45 μm, the refractive index of silicon dioxide is 1.46, the particle size D50 is 35 μm, the total mass of each layer is 100%, the total number of layers is 5, and the specific composition is shown in Table 1;
[0214] The preparation method is as follows:
[0215] (1) Ingredients
[0216] The batching method is the same as in Example 1;
[0217] (2) Molding
[0218] The cavity material is dry pressed at 10 MPa, and then cold isostatically pressed at 200 MPa for 1 min to obtain a green body;
[0219] (3) Sintering
[0220] The green body was placed in a sintering furnace and sintered at 1200° C. to obtain a porous ceramic skeleton with a porosity of 45%.
[0221] Comparative Example 3
[0222] Titanium dioxide powder (refractive index 2.72, particle size 10 μm) was selected for granulation, dry pressed at 8 MPa, and then isostatically pressed at 290 MPa for 1 min. A porous ceramic skeleton with a porosity of 40% was obtained by sintering at 1300°C.
[0223] Comparative Example 4
[0224] The porous ceramic skeleton is composed of leucite glass-ceramics (main powder), hydroxyapatite (secondary powder) and colorants (specifically zirconium iron red, iron yellow and cobalt black), wherein the refractive index of leucite glass-ceramics is 1.49, the particle size D50 is 5 μm, the refractive index of hydroxyapatite is 1.6, the particle size D50 is 5.7 μm, the total mass of each layer is 100%, the total number of layers is 3, and the specific composition is shown in Table 1;
[0225] The preparation method is as follows:
[0226] (1) Ingredients
[0227] The batching method is the same as in Example 1;
[0228] (2) Molding
[0229] The cavity material was dry pressed at 10 MPa, and then cold isostatic pressed at 290 MPa for 1 min to obtain a green body;
[0230] (3) Sintering
[0231] The green body was placed in a sintering furnace and sintered at 780° C. to obtain a porous ceramic skeleton with a porosity of 32%.
[0232] Table 1 Formula, sintering conditions and porosity of porous ceramic skeleton of Examples 1 to 5 and Comparative Examples 1 to 4
[0233]
[0234]
[0235]
[0236] Application Examples 1 to 7
[0237] The porous ceramic skeletons prepared in Examples 1 to 7 are respectively used to prepare resin-infiltrated ceramic composite materials, that is, Application Example 1 uses the porous ceramic skeleton of Example 1, Application Example 2 uses the porous ceramic skeleton of Example 2, and so on. The preparation process is as follows:
[0238] (1) Preparation of modified solution: 500 g of deionized water and ethanol were weighed and mixed uniformly, 0.5 g of acetic acid was added to the above solution, and after stirring uniformly, 30 g of γ-methacryloxypropyltrimethoxysilane (KH-570) was added and stirred for 30 min to obtain a modified solution;
[0239] (2) placing the porous ceramic framework prepared in Examples 1 to 7 in the above-mentioned modified solution, evacuating the solution and maintaining the pressure for 30 minutes, and then drying the framework at 80° C.;
[0240] (3) According to the formula table (Table 2), Bis-GMA, Bis-MEPP, and UDMA were weighed and placed in a beaker, and TEGDMA and BPO were then added to the beaker. The mixture was stirred at 300 r / min for 60 min with an electric stirrer under a 45° C. water bath condition to make the solution uniform. The mixed resin was placed under vacuum to remove bubbles, and a resin material was obtained;
[0241] (4) immersing the obtained modified porous ceramic skeleton in a resin material and infiltrating under vacuum conditions so that the resin completely penetrates into the porous ceramic skeleton;
[0242] (5) The infiltrated resin-infiltrated ceramic is placed in a 200 MPa, 70°C temperature for 6 h, and then heated to 100-130°C at a rate of 2°C / min and kept for 6 h to solidify the resin, thereby obtaining a resin-infiltrated ceramic composite material.
[0243] Table 2 Resin formulations of application examples 1 to 7 and comparative application example 3
[0244]
[0245] Application Comparative Examples 1 to 4
[0246] The porous ceramic skeletons of Comparative Examples 1 to 4 were respectively used to prepare resin-infiltrated ceramic composite materials, and the preparation method was the same as that of Application Example 1, wherein the resin formula of Comparative Example 1 was the same as that of Application Example 1, the resin formula of Comparative Example 2 was the same as that of Application Example 2, the resin formula of Comparative Example 4 was the same as that of Application Example 5, and the resin formula of Comparative Example 3 was shown in Table 2.
[0247] The refractive index of the resin formulations used in Application Examples 1 to 7 and Application Comparative Example 3 is shown in Table 3.
[0248] Table 3 Refractive index of resin formulations of application examples 1 to 7 and application comparison example 3
[0249] Application Example 1 Application Example 2 Application Example 3 Application Example 4 Application Example 5 Application Example 6 Application Example 7 Application Comparative Example 3 1.50 1.51 1.53 1.48 1.49 1.48 1.51 1.50
[0250] Performance Evaluation
[0251] 1. Characterization methods
[0252] Vickers Hardness: Use Vickers hardness tester to test the hardness of dental materials;
[0253] Wear resistance: Test the wear resistance of materials according to YY / T0113-2015;
[0254] Light transmittance: Light transmittance is tested according to standard GB / T2410-2008, using a haze meter for testing, and the sample size requirement is 30×30×1mm.
[0255] Color difference: The color value is tested by a spectrophotometer, the light source is "D65", the measurement mode is "reflection" and "SCI", and the color measurement value is obtained. The color measurement value includes L*, a* and b* values. The color difference between two adjacent layers (referred to as "color difference value") is calculated according to formula 1:
[0256]
[0257] In Formula 1, L*, a*, and b* values are measured values of chromaticity, and n is the nth layer of material.
[0258] The hardness, wear resistance and transition effect of the resin-infiltrated ceramic composite materials prepared in Application Examples 1 to 7 and Comparative Examples 1 to 4 are shown in Table 4, and the color difference and light transmittance data are shown in Table 5. In Table 4, the transition effect is evaluated by visual observation.
[0259] Table 4 Performance comparison between application examples and comparative application examples
[0260]
[0261] Table 5 Comparison of light transmittance and color difference between application examples and comparative examples
[0262]
[0263]
[0264]
[0265] Result analysis:
[0266] From the results of Application Example 1 and Application Comparison Example 1 in Tables 4 and 5, it can be seen that in Application Example 1, from the neck layer to the cutting end layer, the transmittance gradually increases, the color gradually becomes lighter, and the transition between the layers is relatively natural; in Application Comparison Example 1, from the neck layer to the cutting end layer, there is a trend of the transmittance changing from high to low and then gradually increasing. The main reason is that from the neck layer to the B layer, the sodium aluminum silicate content exceeds 50% as the main powder, and the feldspar content gradually increases, resulting in a gradual decrease in the proportion of sodium aluminum silicate, which reduces the transmittance of the material in turn; from the B layer to the cutting end layer, the feldspar content exceeds 50% as the main powder, and the feldspar content continues to increase, which reduces the scattering of light passing through the material and improves the transmittance of the material.
[0267] By comparing Application Example 2 and Application Comparison Example 2, it can be seen that in Application Example 2, the transition between the layers from the neck layer to the cutting end layer is relatively natural, while in Application Comparison Example 2, ceramic particles are vaguely observed. The ceramic particles are relatively large in size, resulting in an unnatural transition between the layers of the material and a sharp drop in its hardness and wear resistance.
[0268] It can be seen from the application of Comparative Example 3 that the refractive index of titanium dioxide is 2.72, while the refractive index of resin is 1.50. The difference between the refractive indices is large, and the linear transmittance of the material is low, resulting in very poor light transmittance of the material.
[0269] By comparing Application Example 5 and Comparative Application Example 4, it can be found that when the mass ratio of the main powder to the secondary powder is the same, excessive addition of colorant causes a decrease in the linear transmittance of the material.
[0270] It can be seen from Application Example 6 that the refractive index of the resin is 1.48. From the neck layer to the cut end layer, the refractive index of the powder changes from 1.60 to 1.48. The difference between the refractive index of each layer and the resin decreases successively, and the transmittance increases successively. This shows that the closer the refractive index of the powder is to the resin to be filled, the higher the transmittance of the material.
[0271] It can be seen from Application Example 7 and Application Example 2 that when the mass ratio of the main powder and the secondary powder is the same and the porosity is the same, the hardness and wear resistance of the material are significantly improved after adding the toughening component.
[0272] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A resin-infiltrated ceramic composite material, characterized in that: It is composed of a multi-layer structure, each layer comprising a porous ceramic skeleton and a resin infiltrated in the pore structure of the porous ceramic skeleton; From top to bottom, the light transmittance of each layer of the resin-infiltrated ceramic composite material increases successively, the absolute value of the difference in light transmittance between two adjacent layers is 0.5-10%, and the absolute value of the difference in light transmittance between the uppermost layer and the lowermost layer is greater than 3%; From top to bottom, the colors of the layers of the resin-infiltrated ceramic composite material gradually become lighter, the color difference between two adjacent layers is 0.5-11, and the color difference between the uppermost layer and the lowermost layer is 1-30.
2. The resin-infiltrated ceramic composite material according to claim 1, characterized in that: The porous ceramic skeleton is obtained by forming and sintering several layers of materials; Measured in percentage by mass, each layer of material in the porous ceramic skeleton independently includes 0-30% colorant, 0-20% toughening agent and the remainder of ceramic powder; and the darkest material layer is the topmost layer, and from top to bottom, the mass proportion of the colorant in the several layers of material decreases successively.
3. The resin-infiltrated ceramic composite material according to claim 2, characterized in that: Each of the several layers of materials contains only one type of ceramic powder; or n-1 layers of materials in the several layers of materials contain two types of ceramic powders, and the remaining layer of materials contains one or two types of ceramic powders, where n is the number of material layers, and n≥2; When each of the several layers of materials contains only one type of ceramic powder: The refractive index of the ceramic powder in each layer of material is independently 1.3 to 1.7; Taking the material layer with the darkest color as the top layer, the absolute value of the difference between the refractive index of the ceramic powder and the refractive index of the resin in each layer of material decreases from top to bottom; When n-1 layers of the plurality of material layers contain two kinds of ceramic powders, and the remaining layer of material contains one or two kinds of ceramic powders: The two kinds of ceramic powders are a first ceramic powder and a second ceramic powder; the refractive index of the first ceramic powder is 1.3 to 1.7; the refractive index of the second ceramic powder is 1.3 to 2.5; When the refractive index of the second ceramic powder is 1.3-1.7, the ceramic powder accounts for ≥50% by weight of the ceramic powder in each layer, and the ceramic powder is used as the main powder, and the other is used as the secondary powder; When the refractive index of the second ceramic powder is greater than 1.7 and less than or equal to 2.5, the mass proportion of the first ceramic powder in the ceramic powder in each layer of material is greater than or equal to 33%; the first ceramic powder is used as the main powder and the second ceramic powder is used as the secondary powder; The material layer with the darkest color is taken as the uppermost layer, and from top to bottom, the mass ratio of the main powder to the secondary powder in the several layers of materials increases successively.
4. The resin-infiltrated ceramic composite material according to claim 3, characterized in that: When each of the plurality of material layers contains only one type of ceramic powder, the particle size D50 of the ceramic powder in each material layer is independently 50 nm to 60 μm.
5. The resin-infiltrated ceramic composite material according to claim 3, characterized in that: The particle size D50 of the main powder is 50nm-60μm; the particle size D50 of the secondary powder is 10nm-30μm.
6. The resin-infiltrated ceramic composite material according to claim 2, characterized in that: The absolute value of the difference in mass percentage of the colorant in two adjacent layers of the plurality of layers of material is ≤15%.
7. The resin-infiltrated ceramic composite material according to claim 3, characterized in that: The absolute value of the difference in mass proportion of the main powder and the absolute value of the difference in mass proportion of the secondary powder in two adjacent layers of materials are both ≤20%.
8. The resin-infiltrated ceramic composite material according to claim 3, characterized in that: The first ceramic powder includes one of feldspar, nepheline, quartz, sodium aluminum silicate, hydroxyapatite, fluoroapatite, glass ceramics and porcelain powder; The second ceramic powder includes one of feldspar, nepheline, quartz, sodium aluminum silicate, hydroxyapatite, fluoroapatite, glass ceramics, porcelain powder, metal oxide, metal sulfate and metal carbonate.
9. The resin-infiltrated ceramic composite material according to claim 8, characterized in that: The feldspar includes one of potassium feldspar, sodium feldspar, calcium feldspar, orthoclase, microcline and sanuclear feldspar; The glass ceramics include one of borosilicate glass, aluminosilicate glass and fluoroaluminosilicate glass; Porcelain powder includes leucite glass-ceramic powder or feldspar porcelain powder; The metal oxide includes one or more of zinc oxide, calcium oxide, magnesium oxide, aluminum oxide, yttrium oxide, zirconium oxide, titanium dioxide, cerium dioxide and niobium oxide; The metal sulfate includes calcium sulfate or aluminum sulfate; The metal carbonate includes calcium carbonate.
10. The resin-infiltrated ceramic composite material according to claim 2, characterized in that: The colorant includes one or more of ferrozirconium red, chrome tin red, ferrosilicon red, iron red, cobalt black, iron black, vanadium yellow, zirconium spectrum yellow, vanadium tin yellow, orange yellow and iron yellow.
11. The resin-infiltrated ceramic composite material according to claim 2, characterized in that: The toughening agent includes inorganic fibers.
12. The resin-infiltrated ceramic composite material according to any one of claims 2 to 11, characterized in that: The number of layers of the material is more than 3; taking the total mass of all layers of material as 100%, the mass proportions of the uppermost layer of material and the lowermost layer of material are independently 16-50%, and the mass proportions of the middle layers of material are independently 10-35%.
13. The resin-infiltrated ceramic composite material according to any one of claims 2 to 11, characterized in that: The porosity of the porous ceramic skeleton is 10-60%.
14. The resin-infiltrated ceramic composite material according to claim 1, characterized in that: Calculated by mass percentage, the raw materials for preparing the resin include 97-99.9% of monomers and 0.1-3% of initiators; the refractive index of the resin is 1.4-1.
7.
15. The resin-infiltrated ceramic composite material according to claim 14, characterized in that: The monomers include a main monomer and a diluent monomer; the mass ratio of the main monomer to the diluent monomer is 0.5 to 9:1; The main monomer is one or more of bisphenol A glycidyl methacrylate, ethoxylated bisphenol A dimethacrylate and urethane dimethacrylate; The diluent monomer includes one or more of triethylene glycol dimethacrylate, ethylene glycol dimethacrylate and trimethylolpropane triacrylate.
16. The resin-infiltrated ceramic composite material according to claim 14, characterized in that: The initiator includes a thermal initiator and / or a photoinitiator.
17. The method for preparing the resin-infiltrated ceramic composite material according to any one of claims 1 to 16, characterized in that: The following steps are involved: The porous ceramic skeleton is immersed in a resin raw material for vacuum infiltration, and the resin raw material is infiltrated into the porous ceramic skeleton and then solidified to obtain the resin-infiltrated ceramic composite material.
18. The preparation method according to claim 17, characterized in that: The method for preparing the porous ceramic skeleton comprises the following steps: The colorant, toughening agent and ceramic powder are mixed according to the proportion to obtain materials for each layer; The materials of each layer are stacked and laid flat, and then pressed into shape to obtain a green body; The green body is sintered to obtain the porous ceramic skeleton.
19. The preparation method according to claim 17, characterized in that: Before the vacuum infiltration, the porous ceramic skeleton is also subjected to coupling modification.
20. The preparation method according to claim 18, characterized in that: The compression molding comprises sequentially performing dry pressing and cold isostatic pressing; The dry pressing pressure is 1 to 20 MPa; The cold isostatic pressing pressure is 100-300 MPa.
21. The preparation method according to claim 18, characterized in that: The sintering temperature is 700-1600°C.
22. Use of the resin-infiltrated ceramic composite material according to any one of claims 1 to 16 or the resin-infiltrated ceramic composite material prepared by the preparation method according to any one of claims 17 to 21 in preparing dental restorations.
Citation Information
Cited By
Fiber-reinforced ceramic photocuring slurry, preparation method and reinforced ceramic material
CN120157463A